IMPLEMENTATION OF BIM IN 3D CADASTRE INTEGRATION ASSET MANAGEMENT AND UTILITY MANAGEMENT - Harpiandi, Andri
Assets and building utility systems must always be maintained and supervised so that they are always in good condition and are not damaged, because if they are negligent in the maintenance process it can result in losses for the building manager. Assets can be goods, equipment, space, or other entities that generate financial or non-financial value for an organization. A building utility system is a completeness of building facilities used to support the achievement of the elements of comfort, health, safety, convenience, communication, and mobility in the building. So the assets and utility systems need to be managed in order to always in good condition. A three-dimensional (3D) cadastral model is required as a solution to provide spatial information or geometric models and information about the interests (rights, restriction, and responsibility) attached to building objects. Three-dimensional geometric models can be obtained through an approach using the Building Information Modeling (BIM) system, because it is considered feasible and has the potential ability to model three-dimensional ownership rights. The three-dimensional frame of the building can be obtained from the results of the recording of the Terrestrial Laser Scanner (TLS) and Handheld Laser Scanner (HLS) which uses light waves to obtain the position of the object's surface. The data generated from the TLS and HLS scans are in the form of point cloud data. The application of the BIM method in 3D cadastral integration, provides information that is directly related to the asset model and utility system, such as information on types, dimensions, owners, and other semantic information attached to the asset model and utility system under study. The collection of semantic attributes of assets and utilities can be used as information for the needs of asset management and utility systems.